A Case Series of diffuse large B-cell lymphoma and burkitt lymphoma presenting with peritoneal lymphomatosis. (2016) - Flores, Everardo; Aydin, Nail; Vu, Duy; Misra, Subhasis
Highlights: Diffuse large B-cell lymphoma (DLBCL) and Burkitt lymphoma can present with peritoneal lymphomatosis in rare cases. Diagnosis cannot be obtained solely by history, physical examination, imaging, and cytology. Biopsy of masses via CT guided imaging and/or laparoscopy can be beneficial in properly diagnosing non-Hodgkin lymphoma. Abstract: Introduction: Non-Hodgkin lymphoma (NHL) can occur at any site of the body, however diffuse and extensive involvement of the peritoneal cavity occurs rarely. Diffuse large B-cell lymphoma (DLBCL) is one of the dominant histological subtypes in extra nodal lymphoma involving the peritoneal cavity while Burkitt lymphoma is seen less commonly. We report two cases of DLBCL and one case of Burkitt lymphoma presenting with peritoneal lymphomatosis (PL). Presentation of case: A retrospective review of two cases involving DLBCL and one case of Burkitt lymphoma with PL was conducted. Findings in all patients were consistent with peritoneal carcinomatosis at initial evaluation. Symptoms included longstanding vague abdominal pain and weight loss. CT imaging along with biopsies showed DLBCL in two cases and Burkitt lymphoma in one case. All three patients were treated with chemotherapy and responded very well. Discussion: We report three cases of non-Hodgkin lymphoma presenting with peritoneal lymphomatosis, a rare phenomena. Due to its nonspecific presentation, laparoscopic biopsies with subsequent pathology analysis should be undertaken as quickly and efficiently as possible to accurate diagnose and treat this condition. Conclusion: DLBCL with PL may have variable and non-specific presentations. It may resemble peritoneal carcinomatosis or other neoplastic and inflammatory conditions. Focused clinical awareness, high level of suspicion, and complementary approach can lead towards accurate diagnosis. Diagnostic laparoscopy plays a crucial role in facilitating diagnosis and treatment.